1996
DOI: 10.1051/parasite/1996034335
|View full text |Cite
|
Sign up to set email alerts
|

Variations dans les taux de lipides plasmatiques en fonction de l'infection àPlasmodium Falciparumà São Tomé

Abstract: Changes in lipid plasma levels during malaria attacks have been proposed for use in diagnosis or to assess the severity of the disease. In order to analyse the plasma levels of cholesterol, triglycerides, HDL-C et LDL-C, we compared, in an endemic area (Sao Tome island), two groups of patients children infected with Plasmodium falciparum (simple malaria attack and cerebral malaria) with a control group of asymptomatic children. No correlation between lipid plasma levels and disease severity was found. Cortelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…Triglycerides were shown to be elevated during malaria infection compared with healthy controls but not statistically significant compared with symptomatic controls. Although the quantity of lipid changes seems to be related to the severity of malaria in some studies [19, 45], others found no correlation [46, 47]. In our study, we identified a positive correlation of lipid-related molecules to parasitemia, reinforcing the finding.…”
Section: Discussionsupporting
confidence: 87%
“…Triglycerides were shown to be elevated during malaria infection compared with healthy controls but not statistically significant compared with symptomatic controls. Although the quantity of lipid changes seems to be related to the severity of malaria in some studies [19, 45], others found no correlation [46, 47]. In our study, we identified a positive correlation of lipid-related molecules to parasitemia, reinforcing the finding.…”
Section: Discussionsupporting
confidence: 87%
“…Subsequently, several clinical studies showed lipid profile changes in the setting of both uncomplicated and complicated malaria [5-10]. Although the magnitude of changes seems to be related to the severity of malaria in several studies [11,12], others found no correlation between the severity of malaria attacks and the extent of lipid profile changes [13,14]. These transient lipid profile changes in the parasitaemic phase have been suggested by some researchers as a potential adjuvant diagnostic tool for malaria [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However there is no relationship between cholesterol and disease severity [134]. In Gabonese children hypertriglyceridaemia is also seen in acute malaria, but as with cholesterol levels there is no relationship with disease severity [134] and triglyceride levels return to normal within a fortnight of treatment. A study of Indian adults also showed that triglycerides were elevated during acute infection.…”
Section: Lipid Metabolism Referencesmentioning
confidence: 99%
“…Hypocholesterolaemia has been noted in adults and children with malaria in Gabon [129][130][131][132][133][134]. HDL-cholesterol is low and LDL-cholesterol remains normal [131].…”
Section: Lipid Metabolism Referencesmentioning
confidence: 99%
See 1 more Smart Citation